Quxie Capsule Inhibits Colon Tumor Growth Partially Through Foxo1-Mediated Apoptosis and Immune Modulation. (April 2019) - Chen, Dongmei; Yang, Yufei; Yang, Peiying
Quxie capsule (QX), a herbal remedy used in traditional Chinese medicine, is routinely used in advanced colorectal cancer treatment in Xiyuan Hospital in Beijing, China. However, the mechanism(s) underlying the effect of QX in colorectal cancer remain unclear, which hampers the optimal use of QX for the treatment of the disease. The transcription factor forkhead box O1 (Foxo1) plays important roles in regulation of cell cycle, apoptosis, and immune response in various cancers. In this study, we examined the antitumor efficacy of QX in a mouse model of colorectal cancer and further investigated the mechanism by which QX regulated Foxo1 protein-mediated pathways. QX administered via gavage daily for 2 weeks in mice carrying CT26 mouse colon tumors resulted in significantly lower mean tumor weight (0.93 ± 0.32 g) compared with that in vehicle control-treated mice (1.57 ± 0.57 g, P <.05). Foxo1 protein expression in tumors was also higher in the QX group than that in the vehicle control group. Furthermore, QX treatment upregulated apoptotic proteins such as Fas, Bim, and cleaved caspase-3 in tumor tissue compared with those in the vehicle control group. Intriguingly, the ratios of Th1/Th2 and Th17/Treg cells and levels of T-bet protein (the key regulator of Th1 and Th2 cells) were higher while the level of Foxp3 (the key regulator of Treg cells) was lower in QX-treated mice compared to vehicle control mice, revealing that Foxo1 upregulated T-bet and downregulated Foxp3 and induced a shift in immune balance. This shift could be critical in the antitumor efficacy of QX. Furthermore, knocking down Foxo1 in human colon cancer HCT116 cells partially blocked the effect of QX-elicited antiproliferative activity. Together, these results suggest that QX exerts antitumor activity in CT26 mouse colon cancer model partially mediated by Foxo1-induced apoptosis and antitumor immune response.